Context- and path-sensitive memory leak detection. - Xie, Yichen (Software engineering notes.)
We present a context- and path-sensitive algorithm for detecting memory leaks in programs with explicit memory management. Our leak detection algorithm is based on an underlying escape analysis: any allocated location in a procedure P that is not deallocated in P and does not escape from P is leaked. We achieve very precise context- and path-sensitivity by expressing our analysis using boolean constraints. In experiments with six large open source projects our analysis produced 510 warnings of which 455 were unique memory leaks, a false positive rate of only 10.8%. A parallel implementation improves performance by over an order of magnitude on large projects; over five million lines of code in the Linux kernel is analyzed in 50 minutes.